2022
DOI: 10.1242/dev.200788
|View full text |Cite
|
Sign up to set email alerts
|

ISL1/SHH/CXCL12 signaling regulates myogenic cell migration during mouse tongue development

Abstract: Migration of myoblasts derive from the occipital somites is critical for tongue morphogenesis. However, the molecular mechanisms of myoblast migration remain elusive. In this study, we report that deletion of Isl1 in the mandibular epithelium leads to aglossia due to myoblast migration defects. Isl1 regulates the expression pattern of chemokine ligand 12 (Cxcl12) in the first branchial arch through the Shh/Wnt5a cascade. Cxcl12+ mesenchymal cells in Isl1ShhCre embryos were unable to migrate to the distal regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…While HH signaling guides embryonic muscle development [71,72], we found no Shh or HHresponding Gli1 expression in postnatal lingual muscles. This argues against direct HH control of tongue muscles, consistent with other studies suggesting stroma-mediated regulation of muscle development [68,69].…”
Section: Gas1 Is the Only Hh Pathway Component Identified In Lingual ...contrasting
confidence: 58%
“…While HH signaling guides embryonic muscle development [71,72], we found no Shh or HHresponding Gli1 expression in postnatal lingual muscles. This argues against direct HH control of tongue muscles, consistent with other studies suggesting stroma-mediated regulation of muscle development [68,69].…”
Section: Gas1 Is the Only Hh Pathway Component Identified In Lingual ...contrasting
confidence: 58%
“…Therefore, we hypothesized that Shh acts downstream of Isl1 to mediate the interaction between the epithelium and the mesenchyme. Previous works have shown that ISL1 regulates the expression of Shh in the tongue and urethral epithelium ( 32 , 33 ). Both RNA-Seq and in situ hybridization results showed that Shh expression in the epithelium was reduced after Isl1 deletion.…”
Section: Discussionmentioning
confidence: 98%
“…HH signaling is essential for embryonic myoblast migration (69, 70). Here we show that neither SHH nor HH signaling is present in the postnatal muscles.…”
Section: Discussionmentioning
confidence: 99%